Self-report questionnaire for the examination of post-traumatic stress reactions in children - Kuterovac-Jagodić, Gordana (1997)
The world-wide increase of children exposed to different kinds of traumata, from intra familial to disaster and war, constitutes major professional and public concern. Childhood exposure to traumatic stress invades on the course of both short term and long term development. Posttraumatic stress disorder has been recognised as a significant source of suffering and has an adverse influence on children's psychological, social and biological development.
The main prerequisite for efficient psychosocial help to children affected by the traumata is the possibility of objective, reliable and valid assessment of different symptoms among the population. The war against Croatia has created the need for the development of such an assessment tool.
After the pilot study, the Questionnaire for the Examination of Post-Traumatic Stress Reactions in Children (Kuterovac-Jagodić, Franc, Vizek-Vidović, 1993) has been administered on a sample of 944 Croatian children aged from 9 to 14 years, all from areas most affected by the war. The questionnaire consists of 20 items and children are required to indicate the frequency of occurrence of PTSD symptoms on a 3-point scale (Never, Sometimes, Always).
Principal component analysis yielded 4 components that explain 43.9% of the variance. The factors are named: "Intrusion and increased arousal", "Changed feelings and behaviour", "Avoidance" and "Numbing". Reliability of the total scale is 0.82. Criterion validity was assessed as the capability of discrimination between children of different objective traumatization. Analyses of variance of the results on the total scale as well as on the four components with factors of gender, age, and level of traumatization indicate that girls, younger and more traumatized children score higher on the questionnaire. Interaction effects were also observed as well as the difference between children who experienced different kinds of war traumata.
Projekt MZOS
ENG